Building the Trail Best Traveled: Effects of Domain Knowledge on Web Search Trailblazing - Yuan, Xiaojun; White, Ryen W. (ACM SIGCHI Conference on Human Factors in Computing Systems (CHI 2012), May 5-10, 2012, Austin, Texas, USA., 2012)
Web users can help guide others through complex tasks in unfamiliar domains by creating ordered sequences of queries and Web pages, an activity we call trailblazing. The trails generated from this process can be surfaced by search engines to help users engaged in these tasks. However, if search engines are going to have people generate trails they need to understand whether there is value in using domain experts for trailblazing (or whether novices are sufficient). In this paper, we describe the findings of a user study of trailblazing in the medical domain, comparing domain novices and experts. We observed differences in how people in each of the groups blazed trails and the value of the trails they generated; experts were more efficient and generated better-quality trails. Although there has been significant research on contrasting novice and expert search behaviors, to our knowledge there is no work (at least in the search domain) on establishing whether artifacts created by do-main experts (trails in our case) are more valuable than those created by novices. The answer to this question is important for system designers who want to learn whether investing in domain expertise is worthwhile.